Service Quality Dimensions and Investors’ Perceptions of DEMAT Account Services in Nepal - Bhim Kumar Thapa,; Ramesh Rasik Paudel,; Murari Karki,; Padam Bahadur Lama, (Interdisciplinary Journal of Management and Social Sciences, 2025)
This study investigates the impact of service quality dimensions on investors' perceptions of DEMAT account services in Nepal. Explanatory research design has been employed with quantitative approach. A structured questionnaire was used to collect primary data among the investors in the Nepal Stock Exchange using convenient sampling method and the constructs were validated for accuracy and reliability. The findings indicate that responsiveness, assurance, empathy, and tangibility significantly influence investor satisfaction and trust, while reliability does not have a notable impact. These results highlight a shift in investor priorities within the digital financial ecosystem. Investors increasingly value quick support, personalized services, and well-designed digital platforms over traditional measures of reliability. This study provides practical recommendations for service providers to enhance customer experiences by focusing on real-time support, fostering trust, and offering user-friendly digital interfaces. By aligning their services with evolving investor expectations, providers can strengthen customer satisfaction and build long-term loyalty in the competitive financial services market. This research contributes to understanding investor behavior and offers insights for improving service quality in digital financial platforms.